Gas Sensor Design Based on a Line Locked Tunable Fiber Laser and the Dual Path Correlation Spectroscopy Method - Everardo Vargas-Rodriguez (Applied Sciences, 2017)
In this work a hybrid gas sensor based on a tunable fiber laser and a correlation spectroscopy technique is presented. The laser is tuned by varying the temperature of a bulk silicon wafer of 85 μ m thickness and, once the desired wavelength is reached the line, is locked by keeping fixed its temperature. According to experimental results the wafer temperature variation was in the order of 0.02 K, which induced an estimated wavelength deviation of 0.12 pm, which satisfies the high wavelength position accuracy required for gas sensing applications. Additionally, it is shown that errors due to laser intensity fluctuations can be minimized by implementing a simple dual path correlation spectroscopy stage. As a proof of the suitability of our tunable fiber laser for gas sensing applications, a C2H2 sensor was implemented. By using a 10 cm gas cell at atmospheric pressure, it was possible to detect concentrations from 0 to 20% with a sensitivity of 521 ppm and sub-minute time response. Moreover, the experimental measurements and simulated results have a high level of agreement. Finally, it is important to point out that, by using doped fiber with different characteristics, other wavelength emissions can be generated.